Usulan Perbaikan Tata Letak Fasilitas Produksi Gudang Tujuh PT. Mulchido Dengan Menggunakan Metode Craft - Erlon Wattimena; Nil Edwin Maitimu (ARIKA, 2015)
In this paper discusses how to do a layout arrangement proposed improvements to the PT. Mulchido from previous layout by using measurements Minimization Material Handling to get the amount of displacement activity displacement is minimal and the costs are low. To get Minimization Material Handling, method Craft used as a tool to solve a problem by calculation using a computer. From the layout of the proposals generated by the algorithm can reduce the moment of displacement craft distance of 11559.35 m to 7671.93 m per month. As for the material handling costs can be minimized from Rp. 14.79236 million, - to Rp. 8,138,161, - per month.